Evaluasi Program Floratama Academy Terhadap Pengembangan Kapasitas UMKM - Maria Tricy Domine Jebaru; Hendrik Toda; David W. Rihi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The Floratama Academy program is an initiative aimed at enhancing the capacity of SMEs in the super-premium tourism area of Labuan Bajo, which faces challenges in competing with larger businesses. This study aims to evaluate the impact of the program on improving the managerial, business, and digital marketing skills of local SMEs. The research method used is a qualitative approach, with in-depth interviews conducted with program participants and organizers. The findings indicate that the Floratama Academy program successfully improved participants' skills in business management, digital marketing, and market access expansion. Several participants reported significant improvements in financial systems, product development, and business revenue growth. In conclusion, the program has a positive impact on the development of SMEs in Labuan Bajo; however, continued mentoring and supportive policies are needed to ensure the long-term sustainability of these positive effects.